A prospective study of acute cerebrovascular disease in the community: the Oxfordshire Community Stroke Project–1981-86. 2. Incidence, case fatality rates and overall outcome at one year of cerebral infarction, primary intracerebral and subarachnoid haemorrhage. Issue 1 (January 1990) - Bamford, J; Sandercock, P; Dennis, M; Burn, J; Warlow, C
Abstract : The age and sex specific incidence rates for cerebral infarction, primary intracerebral haemorrhage and subarachnoid haemorrhage in a population of approximately 105, 000 are presented. Over four years 675 patients with a first-ever stroke were registered with the Oxfordshire Community Stroke Project. The pathological diagnosis was confirmed by computerised tomography (CT) scan, necropsy or lumbar puncture (cases of subarachnoid haemorrhage only) in 78% of cases and a further 17% were diagnosed according to the Guy's Hospital Stroke Diagnostic Score. The proportion of all first-ever strokes by pathological type was: cerebral infarction 81% (95% confidence interval 78-84), primary intracerebral haemorrhage 10% (8-12), subarachnoid haemorrhage 5% (3-7) and uncertain type 5% (3-7). These proportions are similar to other community-based studies. The overall 30 day case fatality rate was 19% (16-22), that for cerebral infarction being 10% (7-13), primary intracerebral haemorrhage 50% (38-62) and subarachnoid haemorrhage 46% (29-63). One year post stroke 23% (19-27) with cerebral infarction were dead and 65% (60-70) of survivors were functionally independent. The figures for primary intracerebral haemorrhage were 62% (43-81) dead and 68% (50-86) of survivors functionally independent and for subarachnoid haemorrhage were 48% (24-72) dead and 76% (56-96) of survivors functionally independent. There are important differences between these rates and those from other sources possibly due to more complete case ascertainment in our study. Nevertheless, the generally more optimistic early prognosis in our study, particularly for cases of cerebral infarction, has important implications for the planning of clinical trials and for the expected impact that any treatment might have on the general population.